Językowy obraz dźwięku (na materiale polsko- i rosyjskojęzycznych recenzji muzycznych) - Dzienisiewicz, Maria (Studia Rossica Posnaniensia, 2021)
The aim of the article is to present the ways of conceptualization of sound in Polish and Russian musical critical texts. For the purpose of the article 145 examples in Polish and 145 examples in Russian were analyzed. The material has been divided into three groups based on the type of sense: a visual approach to sound impressions, a tactile approach to sound impressions and a tastebased approach to sound impressions. The analyzed research material was presented with the use of the linguistic worldview methodology, and grouped into categories. The results of the comparative analysis showed a multiplicity of similarities in the types of categories, as well as in the types of synaesthetic metaphors. The largest groups of conceptualizations are those with Aristotelian origin: QUALITY, SUBSTANCE and SHAPE. Synaesthetic metaphors based on the visual approach to sound impressions proved to be the most widespread. The analyzed texts have provided a huge variety of conceptualizations and synaesthetic metaphors in Polish and Russian musical critical texts which constitute a part of the linguistic worldview of sound.